PERUBAHAN MAKNA LEKSIKAL DALAM PEMAKAIAN BAHASA ARAB (Studi Kasus Pondok Modern Gontor) - Hisyam Zaini (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
Modern Islamic Boarding School of Gontor, commonly called Pondok Gontor, is the pioneer of language teaching among pondok pesantrens– islamic boarding schools- in Indonesia. Its reputation is well known nationally and internationally. There have been many researches on its education systems, yet no particular concerns have been given to the study of language used among santris (students of pesantren). For this concern, this paper aims to study the internal condition of language used daily by santris in their daily life. This paper focuses on semantic changes, which occur in santri’s daily language. Due to the usage of Arabic—the language that is the most commonly used by santris— the main focus of this paper is lexical semantic changes in Arabic language. In additions, this paper analyzes the problems in using words. This paper finds that semantically some words are used incorrectly. For example, some nouns are used as verbs, and some other as adjectives. The semantic changes occur amongst santris seem to be influenced by their first language or their mother tongue. Deeper study needs to be conducted in order to get a whole description of the usage of language by the santris.